Edutainment Tools For Deaf And Impairment Hearing Children : A Survey - Rahmalan, Hidayah; Chong, Wei Shin; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida; Zainal Abidin, Zaheera; Shibghatullah, Abdul Samad; Naim @ Mohayat, Mohd Hariz (American Scientific Publishers, 2018)
Normally,children will start to play with combination of words at the age of twenty-four month and deaf or impairment hearing children born in deaf parents using combined sign to form sentence around eighteen month. Unfortunately,group of deaf or impairment hearing children with their hearing parents,start to learn language skill at very late stage due to they have less or no exposure and environment to learn sign language. During the stage of four to six years old,children need to obtain enough if not excessive information on language.Fail to do so,it will results in difficulties for their language skill development for the whole life. However,they might able to start learning sign language from school if they are lucky enough,or else,the situation becomes critical as they had to go through the hardship in language skill development.There are studies that show children who learn through software games may improve their thinking skills,fast-paced,immensely compelling and rewarding which this suggest us to teach these deaf children, using edutainment tools may help them to engage in learning and study becomes more fun. Therefore,this study also presents a survey on educated and enjoyable tools for deaf and impairment hearing children to teach sign language which is suitable to children and be helpful to those children.